68Ga-DOTA.SA.FAPI as a Potential, Noninvasive Diagnostic Probe for Recurrent and Metastatic Adrenocortical Carcinoma: A Head-to-Head Comparison With 18F-FDG. (20th April 2023) - Chopra, Sejal; Walia, Rama; Mathur, Yamini; Roesch, Frank; Moon, Euy Sung; Rana, Nivedita; Pandey, Somit; Chatterji, Debajyoti; Kumar, Rajender; Singh, Harmandeep; Mittal, Bhagwant Rai; Shukla, Jaya
Abstract: Metastatic or recurrent adrenocortical carcinoma (ACC) is a potentially fatal malignancy, which poses major challenges in disease management owing to lack of effective systemic therapies. The drastically reduced survival rates require prompt identification of selective molecules for development of targeted therapeutics. We evaluated the squaric acid containing FAPI derivative, DOTA.SA.FAPI (FAPI), as a potential diagnostic probe in 2 cases of histopathologically proven metastatic and recurrent ACC. Both patients underwent 18 F-FDG and 68 Ga-FAPI PET/CT scans for comparative analysis. 68 Ga-DOTA.SA.FAPI emerged as an excellent diagnostic agent for ACC and performed similar to 18 F-FDG.